Global Health Policy and Access to Care: Investigating Patient Choice on an International Level Using Social Media - Zhukovsky, Peter; Ruggeri, Kai; Garcia-Garzon, Eduardo; Plakolm, Sara; Haller, Elisa; Petrova, Dafina; Mahalingam, Vaishali; Menezes, Igor G. (Frontiers in Public Health, 2016)
Background: The increased access to transportation and information has led to the emergence of more diverse patient choice and new forms of healthcare consumption, such as medical travel. In order for healthcare providers to effectively attract patients, more knowledge is needed on the mechanisms underlying decision-making of potential travelers from different countries. A particularly promising method of studying the travelers’ motives is collecting data on social media. Objectives: The aim of this study was to test what factors influence decision-making of potential medical travelers and how these factors interact. The factors analyzed included quality, cost, and waiting time for two procedures varying in invasiveness across twelve different destination countries. Methods: Decision-making patterns were examined using a pilot questionnaire that generated a large amount of data from over 800 participants in 40 countries. Participants indicated their willingness to travel given different scenarios. Each scenario consisted of a combination of several factors. Additionally, participants were asked to indicate the reasons for their choice. Results: Individuals display surprisingly high willingness to travel for medical care (66.9% agreed to travel across scenarios). Among the factors influencing their decisions, quality of the medical procedure abroad was considered most important, and cost was least important as shown by chi-square tests and corresponding odds ratios. Loglinear analyses revealed an interaction between time waiting in the local healthcare system and type of procedure, whereby time pressure increased the odds of agreeing to travel for the more invasive procedure. The odds of travelling to Europe and the USA were by far the highest, although participants indicated that under certain conditions they might be willing to travel to other medical destinations such as Asia. Conclusions: Our measurements yielded several reliable insights into the factors driving medical decision-making. An essential next step would be to expand these findings with a more encompassing sample and more elaborate statistical modelling.